Cox, Jessica. Neo-Victorianism and Sensation Fiction. Cham: Palgrave Macmillan, 2019. 251 pp. ISBN: 978-3-030-2989-8 - Demirel, Özlem (FOCUS: Papers in English Literary and Cultural Studies, 2022)
Sensation fiction was irresistibly popular yet problematic during the nineteenth century, often because it attempted to subvert nineteenth-century values and social norms and scandalized Victorian society. Its contestable position and the intricate relationship with the historical period that created the genre itself made sensation fiction a distinctive genre in both academic and popular interest in Victorian literary studies. Its enormous influence on twentieth- and twenty-first-century literature and the apt for reading Victorians from a contemporary and postmodern perspective show the acknowledgement of the genre in critical discourse.